Students Writing Anxiety and Its Correlation with Writing Performance - Kismia Septiani (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This present study aims to examine the correlation between students’ writing anxiety and their writing performance; moreover, it is also to find out the level and the type of students’ writing anxiety. The data were obtained from 60 English students of second semester at University of Islam Malang by administering a questionnaire. This study applied a quantitative approach, which used a questionnaire of SLWAI by Cheng (2004) and a document of writing score as the instruments. The data were analyzed by using SPSS 14. The results of this study showed that somatic anxiety (M= 22.72) was mostly faced by the students, followed by avoidance behaviour (M= 19.32) and cognitive anxiety (M= 18.43). The overall mean score is 60.37, which means that the level of students’ anxiety is at a moderate level. Furthermore, this study proved that there was no significant correlation between students’ writing anxiety and their writing performance with the p-value is 0.105 (>0.05). It can be interpreted that the students’ writing anxiety does not affect students’ writing performance.Keywords: Writing anxiety, writing performance, SLWAI